Influence of Men's Attitudes toward Health and Health Insurance on Prostate Specific Antigen Screening for the Early Detection of Prostate Cancer. Issue 6 (November 2019) - Rezaee, Michael E.; Ward, Charlotte E.; Pais, Vernon M.; Dagrosa, Lawrence M.
Abstract: Introduction: The majority of guidelines currently recommend shared decision making for men 55 to 69 years old who are considering prostate specific antigen screening, and proceeding based on values and preferences. Qualitative studies have shown that negative attitudes toward physicians, health care and general health can influence decisions to pursue prostate specific antigen screening. We evaluated the impact of men's attitudes toward health and health insurance on prostate specific antigen screening. Methods: A retrospective secondary data analysis was conducted of men 55 to 69 years old without a history of prostate cancer using 2015 Medical Expenditure Panel Survey data. The relationships between 4 survey statements pertaining to attitudes toward health and health insurance and prostate specific antigen screening in the last 2 years were assessed using multiple logistic regression. Results: The analysis sample consisted of 1, 771 men which equated to 20, 498, 788.2 once weighted, and of these men 63.1% underwent prostate specific antigen screening. Men who agreed 1) they did not need health insurance (OR 0.67, 95% CI 0.47–0.95), 2) health insurance was not worth the money it costs (OR 0.75, 95% CI 0.56–0.99), 3) they were more likely to take risks than the average person (OR 0.73, 95% CI 0.54–0.98) and 4) they could overcome illness without help from a medically trained person (OR 0.55, 95% CI 0.41–0.72) had significantly decreased adjusted odds of undergoing prostate specific antigen screening. Conclusions: Men with negative attitudes toward health and health insurance have significantly decreased odds of undergoing prostate specific antigen screening. With increased emphasis being placed on patient values, preferences and shared decision making, clinicians should assess for negative attitudes toward health and health insurance and intervene with these men to optimize the delivery of preventive care.